Metallogeny of the Yi’nan Tongjing Au–Cu skarn deposit, Luxi district, North China Craton: Perspective from in-suit trace elements, sulfur and lead isotopes of sulfides - Cai, Wen-Yan; Zhang, Zhao-Lu; Liu, Xiao; Gao, Ji-Lei; Ma, Ming; Li, Yadong; Song, Ying-Xin; Li, Zeng-Sheng (Frontiers in Earth Science, 2023)
Gold–Cu skarn deposits are characterized by a diverse mineral assemblage, whose in-situ major/trace elements and isotope compositions can provide key constraints to the migration and enrichment of Au during hydrothermal processes. The Yi'nan Tongjing Au–Cu deposit is located in the central part of the Luxi district, and both skarn and Au–Cu ore bodies occur at the contact between the Early Cretaceous diorite porphyry and the Neoproterozoic to Cambrian carbonate rocks. Five stages of mineralization were identified: (I) early skarn (garnet–diopside–wollastonite); (II) late skarn (magnetite–epidote–actinolite±tremolite); (III) oxide (specularite–hematite); (IV) sulfide (pyrite–chalcopyrite–sphalerite–quartz–chlorite); and (V) late quartz–calcite. The mineralization process in the Tongjing Au-Cu deposit was revealed by detailed scanning electron microscope-backscattered electron imaging, electron probe microanalysis, in-situ trace element, sulfur and lead isotope analysis. Magnetite is enriched in chalcophile elements (Cu, Zn, Pb), Co and Ni, probably due to hydrothermal overprint. The substitution of As and other elements in the formation of pyrite is conducive to the entry of Au into pyrite. The increase of Se and As contents in pyrite from stage IVa to IVb indicates that the temperature, salinity and oxygen fugacity of the ore-forming fluid decrease while the pH rises, resulting in the unloading of Au. The temperature of Au mineralization based on the Se content in pyrite does not exceed 300 °C. Furthermore, V positively correlated with Ti and Ni/Cr ratios ≥1 in magnetite and most Co/Ni ratios in pyrite > 10 all confirm their hydrothermal origins. The restricted sulfur (δ34SV-CDT = -0.5–1.2‰; mean = 0.4‰) and lead (206Pb/204Pb = 17.323–17.383; 207Pb/204Pb = 15.424–15.452; 208Pb/204Pb = 37.367–37.454) isotopic compositions suggest that the deep magma provided the primary mineralized material, accompanied by a relatively small amount of shallow crustal material. The Yi'nan Tongjing Au–Cu skarn deposit was formed in the Early Cretaceous, which is an important metallogenic response to the strong decratonization of the North China Craton induced by the paleo-Pacific Plate roll-back. This study shows that there is a large potential of Early Cretaceous skarn mineralization in the Luxi district.